The Fourth Lateran Council as the Main Agenda for the Preparation of the Fifth Crusade - Okky Chandra (Diligentia: Journal of Theology and Christian Education, 2020)
The Latin Church in medieval time regarded crusades as holy wars against paganism and heretics. Pope Innocent III was one of the church leaders who strongly believed that Christians need to regain the Holy Land. After initiating the Fourth Crusade and was disappointed by the failure of the crusaders, Innocent III organised the Fourth Lateran Council for the main purpose of launching the Fifth Crusade. While some scholars maintained that the reform of universal church was one of the main agenda of the Council, this paper shows that it was ancillary to the preparation of all elements within the Church for the next Crusade.